Research on Dynamic Resource Scheduling Technology of Dispatching and Control Cloud Platform Based on Container - Liu, Dong; Huang, Yunhao; Wang, Jiaqi; Xia, Wenyue; Li, Dapeng; Feng, Qiong (Big Data Analytics for Cyber-Physical System in Smart City, 2021)
With the continuous advancement of dispatching and control cloud, traditional platform systems and virtualization technologies have been well supported in resource scheduling, flexible scaling, rapid migration deployment, the future availability and maintainability of these business systems will face enormous challenges. The rapid development of Docker container technology has solved the shortcomings of traditional PaaS platform based on virtual machine. In this paper, Docker container technology is used to build PaaS platform services of dispatching and control cloud. Through the analysis and verification of the flexible scaling, resource scheduling, container response and other performance aspects of the container, the experiment shows that the Docker-based PaaS platform has a good effect in the rational scheduling, rapid response and flexible scaling of resources.